1993
DOI: 10.1152/ajpendo.1993.265.2.e243
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in levels of Na(+)-K(+)-ATPase isoforms in heart, skeletal muscle, and kidney of diabetic rats

Abstract: In streptozotocin (STZ)-induced diabetic rats, activities of Na(+)-K(+)-ATPase and the Na pump have been shown to be altered. Cellular mechanisms underlying such changes remain unclear. The present studies examined by immunoblotting the levels of Na(+)-K(+)-ATPase subunit isoforms in heart, skeletal muscle, and kidney of diabetic rats. Effects of insulin treatment on these levels were also studied. In cardiac muscle, STZ-induced diabetes caused a marked decrease in alpha 2-levels, a moderate decrease in beta 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 26 publications
4
34
0
Order By: Relevance
“…The reduction in Na,K-ATPase activity was consistent with the results of a previous study using the same experimental model with a different enzymatic assay, i. e. measurement of K-stimulated pNPPase, which is a partial reaction of the Na,K-ATPase enzymatic cycle [9]. The observation of a decreased Mg-ATPase activity in native vesicles could be related to the sensitivity of enzyme activity to lipid environments.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The reduction in Na,K-ATPase activity was consistent with the results of a previous study using the same experimental model with a different enzymatic assay, i. e. measurement of K-stimulated pNPPase, which is a partial reaction of the Na,K-ATPase enzymatic cycle [9]. The observation of a decreased Mg-ATPase activity in native vesicles could be related to the sensitivity of enzyme activity to lipid environments.…”
Section: Discussionsupporting
confidence: 90%
“…The two isoenzymes appear to be specifically affected by these two parameters. Ng et al [9] studied changes caused by STZ-induced diabetes on expression of cardiac Na,K-ATPase subunit isoforms and reported that a 2 and b 1 protein expression decreased while a 1 protein expression remained unchanged. The Northern blot analysis confirms these results on protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several isoforms of Na + /K + -ATPase exist from different combinations of the α and β subunits [22]. In the streptozotocin (STZ) rat model of diabetes, increased muscle α2 subunit mRNA [23] and protein concentrations [24] with no change or decrease of enzyme activity were observed in skeletal muscle. The increase in α2 mRNA concentration was thought to be a compensatory increase due to the decreased Na + /K + -ATPase activity under hypoinsulinaemic state, which occurred in the STZ-induced diabetes or after 48-h fasting in rats [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has also been demonstrated that in the heart, streptozotocin-induced diabetes caused a conspicuous reduction in enzyme activity with a marked decrease of alpha 2 [13]. In an earlier study, Fawzi and McNeill [14] reported a decrease of both low and high affinity ouabain binding sites in left ventricle obtained from chronically diabetic rats.…”
mentioning
confidence: 95%